2015
DOI: 10.1097/mop.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origins of health and disease

Abstract: Purpose of Review While diseases may appear clinically throughout the lifespan, it is clear that many diseases have origins during development. Altered nutrition, as well as exposure to environmental chemicals, drugs, infections, or stress during specific times of development can lead to functional changes in tissues, predisposing those tissues to diseases that manifest later in life. This review will focus on the role of altered nutrition and exposures to environmental chemicals during development in the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
116
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(123 citation statements)
references
References 51 publications
3
116
0
4
Order By: Relevance
“…Several studies have already documented that hundreds of epi-genotoxic molecules, present in the placentas and umbilical cords, interfere with cell and tissue programming. This field of investigation supports the Developmental Origins of Health and Disease theory (DOHaD), based on the concept that the ‘early life environment’ has remarkable consequences for the adult health [1]. In particular, it is suggested that fetal cells might undergo reactive epigenetic changes, which represent potentially adaptive-defensive responses to environmental factors (fetal programming).…”
Section: Introductionsupporting
confidence: 57%
“…Several studies have already documented that hundreds of epi-genotoxic molecules, present in the placentas and umbilical cords, interfere with cell and tissue programming. This field of investigation supports the Developmental Origins of Health and Disease theory (DOHaD), based on the concept that the ‘early life environment’ has remarkable consequences for the adult health [1]. In particular, it is suggested that fetal cells might undergo reactive epigenetic changes, which represent potentially adaptive-defensive responses to environmental factors (fetal programming).…”
Section: Introductionsupporting
confidence: 57%
“…For example, it is well understood that hormones have very different roles during development compared to adulthood [119, 72], thus EDCs are expected to have more potent effects during critical periods of development [120, 121]. Other environmental chemicals may also have effects that are more profound when exposures occur during development (e.g.…”
Section: A Brief Overview Of the Risk Assessment Process For Edcsmentioning
confidence: 99%
“…There is increasing concern regarding the life-long neurotoxic effects of developmental exposure to environmental contaminants at levels that do not result in acute toxicity (Connors et al, 2008, Grandjean and Landrigan, 2006, 2014, Heindel and Vandenberg, 2015, Lupien et al, 2009). A group of chemicals implicated in such effects are 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD, “dioxin”) and non- ortho (“dioxin-like”) polychlorinated biphenyls (PCBs), ubiquitous contaminants that are present in up to ng/g (lipid-adjusted) quantities in human cord blood and breast milk samples, suggesting fetal or in utero exposure to low levels during early development (Crinnion, 2011, Huisman et al, 1995, Park et al, 2010, Patandin et al, 1999, Schantz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%